Thermic effect of food at rest, during exercise, and after exercise in lean and obese men of similar body weight. - Segal, K R (1985)
The thermic effect of food at rest, during 30 min of cycle ergometer exercise, and after exercise was studied in eight lean (mean +/- SEM, 10 +/- 1% body fat, hydrostatically-determined) and eight obese men (30 +/- 2% body fat). The lean and obese mean were matched with respect to age, height, weight, and body mass index (BMI) to determine the relationship between thermogenesis and body composition, independent of body weight. All men were overweight, defined as a BMI between 26-34, but the obese had three times more body fat and significantly less lean body mass than the lean men. Metabolic rate was measured by indirect calorimetry under four conditions on separate mornings, in randomized order, after an overnight fast: 3 h of rest in the postabsorptive state; 3 h of rest after a 750-kcal mixed meal (14% protein, 31.5% fat, and 54.5% carbohydrate); during 30 min of cycling and for 3 h post exercise in the postabsorptive state; and during 30 min of cycling performed 30 min after the test meal and for 3 h post exercise. The thermic effect of food, which is the difference between postabsorptive and postprandial energy expenditure, was significantly higher for the lean than the obese men under the rest, post exercise, and exercise conditions: the increments in metabolic rate for the lean and obese men, respectively, were 48 +/- 7 vs. 28 +/- 4 kcal over 3 h rest (P less than 0.05); 44 +/- 7 vs. 16 +/- 5 kcal over 3 h post exercise (P less than 0.05); and 19 +/- 3 vs. 6 +/- 3 kcal over 30 min of exercise (P less than 0.05). The thermic effect of food was significantly negatively related to body fat content under the rest (r = -0.55), post exercise (r = -0.66), and exercise (r = -0.58) conditions. The results of this study indicate that for men of similar total body weight and BMI, body composition is a significant determinant of postprandial thermogenesis; the responses of obese are significantly blunted compared with those of lean men.